Water reuse to free up freshwater for higher‐value use and increase climate resilience and water productivity. (21st February 2022) - Drechsel, Pay; Qadir, Manzoor; Baumann, Jurgen
Abstract: The impact of climate change on the availability of water affects all types of land use and sectors. This complexity calls for integrated water resources management and negotiations between sectors on the most important, cost‐effective, and productive allocation of water where it is a limited resource. This reflection paper shows examples of adaptation efforts to water scarcity at a scale where gains in water productivity can be derived from inter‐sectoral water reuse and wastewater–freshwater swaps, complementing other water scarcity coping strategies (water savings, long‐distance transfer, and desalination). Wastewater treatment for reuse offers opportunities across scales as it allows, for example, donor regions to be compensated with reclaimed water for the release of freshwater for higher‐value use, increasing overall economic water productivity in this way. In such water swaps, farmers are compensated with higher water volumes in exchange for higher quality. The reuse of water between sectors offers opportunities to (i) expand the traditional (agricultural) water productivity concept and (ii) significantly increase water productivity at the system level. While rural–urban water reallocation can help mitigate the impacts of climate change, compensating farmers with reclaimed water remains limited for the reasons discussed in the paper. Abstract: L'impact du changement climatique sur la disponibilité de l'eau affecte tous les types d'utilisation des terres et tous les secteurs. Cette complexité appelle une gestion intégrée des ressources en eau (GIRE) et des négociations entre secteurs sur l'allocation la plus importante, rentable, et productive de l'eau là où celle‐ci est une ressource limitée. Ce document de réflexion montre des exemples d'efforts d'adaptation à la rareté de l'eau à grande échelle où des gains de productivité de l'eau peuvent être dérivés de la réutilisation intersectorielle de l'eau et des échanges d'eaux usées et d'eau douce, en complément d'autres stratégies d'adaptation à la rareté de l'eau (économies d'eau, transfert à longue distance, dessalement). Le traitement des eaux usées pour la réutilisation offre des opportunités particulières car il permet aux régions donatrices d'être compensées par de l'eau récupérée pour la libération d'eau douce pour une utilisation à plus grande valeur, augmentant ainsi la productivité économique globale de l'eau. Dans ces échanges d'eau, les agriculteurs sont indemnisés avec des volumes d'eau plus élevés en échange d'une meilleure qualité. La réutilisation de l'eau entre les secteurs offre des opportunités pour: i) étendre le concept traditionnel de productivité de l'eau [agricole]; ii) augmenter considérablement la productivité de l'eau au niveau du système. Alors que la réallocation de l'eau entre les zones rurales et urbaines peut aider à atténuer les impacts du changement climatique, l'indemnisation des agriculteurs avec de l'eau récupérée reste encore limitée pour les raisons évoquées dans le document.